Cross-Cultural Adaptation of the Administration Instructions of the Developmental Test of Visual Perception 3rd Edition for isiZulu-Speaking Children - Bekker, Maretha (University of Pretoria, 2022)
Dissertation (MSc (Occupational Therapy))--University of Pretoria, 2022.